A study on the types of dehydration and serum sodium level in infants and young children at the time of hospital admission with acute diarrhea in rural area of Jharkhand - Dr. Vishal; Dr. Madhurima Prasad (Pediatric Review: International Journal of Pediatric Research, 2018)
Objectives: This study was done to know the incidence of different type of dehydration clinically in acute watery diarrhea (mild, moderate and severe) along with serum sodium level (isonatraemic, hyponatraemic, hypernatraemic) at presentation in hospital. Method: Prospective observational study done at admission on children below 5years of age with acute watery diarrhea. Dehydration was clinically classified as mild, moderate and severe. Serum sodium level was estimated at admission with Roche cobas autoanalyzer (indirect ISE method) and separated into 3 groups: (1) isonatraemic / hyponatraemic/ hypernatraemic dehydration. Children who had dysentery or diarrhea more than 7 days duration, taken iv fluids, metabolic disease/chronic medical condition were excluded from the study. Results: There were 68 patients in which 64.7% were males.42.6% cases were between 1-2 year of age. 45 cases had moderate dehydration in which 57.7% had isonatraemic dehydration. 23 cases had severe dehydration in which 60.8% had hyponatraemic dehydration. There was no hypernatraemic dehydrated patients among severe dehydration / appropriate ORS or plain water groups. Only 10 (14.7%) cases were taking appropriate oral rehydration therapy in which 60% have isonatraemic dehydration.12 Patients on concentrated ORS had 75% isonatraemic dehydration. 18 Patients on diluted ORS had 55.5% isonatraemic dehydration. Conclusion: About two third had moderate dehydration and majority had isonatraemic dehydration. Very few patients were given appropriate ORS therapy. Thus, we need to educate society about proper domiciliary treatment (appropriate fluid/ORS solution) in case of diarrhoea.